KOJIC ACID PRODUCTION USING MIXED CULTURES OF ASPERGILLUS ORYZAE AND ASPERGILLUS TAMARII - Suryadi, Herman; Sukarna, Dyah Karina Puspita (International Journal of Applied Pharmaceutics, 2018)
Objective: This study aimed to find the optimum kojic acid fermentation conditions using combination cultures of Aspergillus oryzae and Aspergillus tamarii. Methods: Screening of the best mixed cultures was performed using yeast extract medium with 5% (w/v) glucose. Fermentation conditions were optimized by varying carbon and nitrogen sources, pH of medium, inoculum ratio, and aeration. Aeration was varied using 50 and 100 mL of medium in 100 and 250 mL Erlenmeyer flasks, respectively. Kojic acid was analyzed using thin-layer chromatography-densitometry and UV-Vis spectrophotometry. Results: Kojic acid produced from mixed cultures yielded 0.1396 gg−1, while sole cultures of A. oryzae and A. tamarii yielded 0.0329 gg−1 and 0.1001 gg−1, respectively. Of the nine fermentation mediums, the best carbon and nitrogen sources were sucrose and yeast extract. From the three variations of pH, pH 3.5 was the optimum pH value. From the three ratios of inoculum concentration, a ratio of 2:3 (A. oryzae:A. tamarii) was the best ratio. Aeration was varied using 50 and 100 mL of medium in 100 and 250 mL Erlenmeyer flasks, respectively. Aeration of 100 mL medium in 250 mL Erlenmeyer flask was selected as the best aeration that produced 6.559 g/L kojic acid. Conclusion: The highest concentration of kojic acid was obtained by mixing cultures of A. oryzae and A. tamarii in a ratio of 2:3, using sucrose and yeast extract as the substrates at pH 3.5 and semiaerobic condition.